Quality Disclosure Under Consumer Loss Aversion - Zhang, Jianqiang; Li, Krista J. (Management Science, 2021)
Consumers experience a sense of loss when a product’s quality does not match their expectations. To alleviate consumer loss aversion (CLA), firms can disclose information to reduce consumers’ uncertainty about product quality and the resulting psychological loss. In this paper, we investigate the implications of CLA on firm profit, consumer surplus, and social welfare when firms endogenously make quality disclosure decisions. We find that CLA leads symmetric firms to disclose quality more often. Given that CLA weakly reduces consumers’ utility from buying a product and quality disclosure is costly, intuition suggests that CLA is detrimental to firms. We find that this intuition is true only in a monopoly. Surprisingly, CLA makes both firms in a competition better off. Moreover, CLA increases firms’ profit when they invest in quality disclosure instead of money-back guarantees to respond to CLA. We also find that CLA decreases consumer surplus and social welfare. Therefore, educating consumers to improve decision-making skills by deliberating on future outcomes and emotions can benefit firms at the cost of consumers and society. When firms disclose quality sequentially, CLA can discourage the follower from disclosing quality. A strong level of CLA increases the leader’s profit over the follower’s, thereby encouraging firms to be the first mover in quality disclosure. This paper was accepted by Juanjuan Zhang, marketing.